2010
DOI: 10.1111/j.1365-2141.2009.08058.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute leukaemias of ambiguous lineage in children: characterization, prognosis and therapy recommendations

Abstract: SummaryAcute leukaemias of ambiguous lineage (ALAL) represent a rare type of leukaemia, expressing both myeloid and lymphoid markers. This study retrospectively analyzed data from 92 children (biphenotypic n = 78, bilineal n = 6, lineage switch n = 8) with ALAL registered in the Berlin-Frankfürt-Münster (BFM) acute myeloid leukaemia (AML) and acute lymphoblastic leukaemia (ALL) studies between 1998 and 2006 (2AE4% of all cases with acute leukaemia). Our cohort of ALAL patients was characterized by comparativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
101
4
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 31 publications
6
101
4
14
Order By: Relevance
“…In our experience, even when chemotherapy was administered based on immunophenotype findings, this strategy has not overcome the dismal prognosis in any of our patients. However, our cases are somewhat different from those reported by Gerr et al [37], mainly regarding cytogenetics and age. The authors reported that only the three cases with trisomy 8 remained alive following HSCT.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In our experience, even when chemotherapy was administered based on immunophenotype findings, this strategy has not overcome the dismal prognosis in any of our patients. However, our cases are somewhat different from those reported by Gerr et al [37], mainly regarding cytogenetics and age. The authors reported that only the three cases with trisomy 8 remained alive following HSCT.…”
Section: Discussioncontrasting
confidence: 99%
“…The mostly single case pediatric reports in the literature also support this notion, describing switches from Bcp to myelo-monocytic lineages [5,6,9,25,26,[31][32][33][34][35][36][37]. Conversions from AML (or bilineal) to ALL are even more rare [38][39][40][41][42][43], also involve mostly Bcp and myelo-monocytic lineages, as was the case with the 2 patients from our own series that switched from myeloid to Pro-B.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations